Attitude of healthcare professionals towards people with disabilities in Hospital Tengku Ampuan Afzan, Pahang - Ismail, Farhana Fakhira; A Rahman, Norny Syafinaz; Muda, Siti Mariam; M Noor, Zaswiza (International Journal of Children, Women, Elderly and Disable People, 2018)
Attitude of healthcare professionals gives big influence towards self-esteem of people with disabilities. Not treated with respect, not equipped with suitable equipment, and denied health services are some problems encountered by people with disabilities in healthcare setting. Profession, age, gender, years of working experience, and contact with people with disabilities are factors that would affect their attitudes. Thus, this study is aimed to identify general attitude of healthcare professionals from Hospital Tengku Ampuan Afzan (HTAA), Kuantan towards people with disabilities. A descriptive, cross-sectional study was conducted among healthcare professionals from HTAA. A validated questionnaire namely Scale of Attitudes toward Disabled Persons (SADP) was used to collect data from the respondents. Descriptive statistics, independent sample t-test, one-way ANOVA, post hoc analysis and Pearson correlation were used to analyse the data using IBM SPSS Statistics for Windows, version 20. A total of 350 respondents were recruited in this study. Physician was found to have the most favorable attitude followed by optometrist. With respect to gender, male was found to hold significant (p=0.002) more favorable attitudes compared to female. Respondents who have close relatives or family members with disabilities developed more favorable attitude compared with those who do not have (p= 0.32). Besides, it was found that, when the age and years of working experience increase, respondents held less favorable attitude. Weak negative correlation was found between attitude score with both age (r = - 0.154) and working experience (r = - 0.189). Profession, gender, contact with people having disabilities, age and working experience play a role in determining their attitude.